Ethnoclassification of Medicinal Plants and Understanding Health and Disease by the Taote in Rapa Nui - Passalacqua Hucke, Lafquen Karen (2025)
This article analyzes the ethnoclassifications of medicinal plants made by the taote in Rapa Nui. From this perspective, multivocality plays a fundamental role in the creation of this research. Through a qualitative study based on semi-structured interviews and ethnographic records, it examines how the taote (local medical agents) organize and classify plants used in health-disease processes from an emic taxonomy. Different hierarchical levels between plants 'tupuna' (sacred and ancestral), 'own', 'foreign', and 'contemporary' are identified, as well as residual categories (which are not plants but are included as therapeutic elements, such as seawater, mud, sand, stones (maea poro), among others that will be mentioned later).